Training with reduced carbohydrate availability affects markers of bone resorption and formation in male academy soccer players from the English Premier League - Reuben Stables; Liam Anderson; Craig Sale; Marcus P. Hannon; Rachel Dunn; Jonathan C. Y. Tang; William D. Fraser; Nessan B. Costello; Graeme L. Close; James P. Morton (European Journal of Applied Physiology, 2024)
Purpose To test the hypothesis that training with reduced carbohydrate (CHO) availability increases bone resorption in adolescent soccer players. Methods In a randomised crossover design, ten male players (age: 17.4 ± 0.8 years) from an English Premier League academy completed an acute 90-min field-based training session (occurring between 10:30–12:00) in conditions of high (TRAIN HIGH; 1.5 g.kg −1 , 60 g, 1.5 g.kg −1 and 1.5 g.kg −1 consumed at 08:00, during training, 12:30 and 13:30, respectively) or low CHO availability (TRAIN LOW; 0 g.kg −1 ). Participants also completed a non-exercise trial (REST) under identical dietary conditions to TRAIN LOW. Venous blood samples were obtained at 08:30, 10:30, 12:30 and 14:30 for assessment of bone resorption (βCTX), bone formation (PINP) and calcium metabolism (PTH and ACa). Results External training load did not differ (all P > 0.05) between TRAIN HIGH and TRAIN LOW, as evident for total distance (5.6 ± 0.8; 5.5 ± 0.1 km), average speed (81 ± 9; 85 ± 12 m.min −1 ) and high-speed running (350 ± 239; 270 ± 89 m). Area under the curve for both βCTX and PINP was significantly greater ( P < 0.01 and P = 0.03) in TRAIN LOW versus TRAIN HIGH, whilst no differences in PTH or ACa ( P = 0.11 and P = 0.89) were observed between all three trials. Conclusion CHO restriction before, during and after an acute soccer training session increased bone (re)modelling markers in academy players. Despite acute anabolic effects of bone formation, the long-term consequence of bone resorption may impair skeletal development and increase injury risk during growth and maturation.